Autonomous replication of foreign DNA in Histoplasma capsulatum: role of native telomeric sequences. - Woods, J P (1993)
Genetic transformation of the dimorphic pathogenic fungus Histoplasma capsulatum can result in chromosomal integration of the transforming DNA or the generation of multicopy linear plasmids carrying the transforming DNA. We showed previously that Escherichia coli plasmids do not replicate autonomously in H. capsulatum without significant modifications, one of which is the in vivo addition of Histoplasma telomeres at the termini of linear DNA. To address the requirements for autonomous replication in H. capsulatum, we constructed a circular E. coli plasmid containing adjacent inverted stretches of Histoplasma telomeric repeats separated by a unique restriction site. The linearized plasmid bearing telomeric termini was maintained in H. capsulatum without modification other than the addition of more telomeric sequence. We recovered the original plasmid in E. coli after removal of the telomeric termini by using engineered restriction sites. Thus, no special Histoplasma modification or sequence other than the telomeres was needed for autonomous replication in H. capsulatum. Additionally, this plasmid provides a shuttle vector that replicates autonomously in E. coli (as a circular plasmid) and in H. capsulatum (as a linear plasmid).